(untitled) (Journal of Computational Mathematics, 2018)
We study the behavior of some polynomial interior-point algorithms for solving random linear programming (LP) problems. We show that the expected and anticipated number of iterations of these algorithms is bounded above by O(n^1.5). The random LP problem is Todd's probabilistic model with the Cauchy distribution.